Developmental psychology - Leman, Patrick; Bremner, Andy.; Parke, Ross D.; Gauvain, Mary. (London : McGraw-Hill, 2012)
This is an accessible but rigorous textbook, looking at development through the lifespan, with a focus on childhood and adolescence. Organised by topic, the book concentrates on core areas within each stage of development.
Includes bibliographic references and index.
Keywords: Developmental psychology